Review and classification of human gait training and rehabilitation devices - Martins, Maria M. (2011)
The number of people with reduced mobility capabilities increases every year. This reduction arises mainly due to spinal cord injuries; strokes which caused hemiparesis; or due to an advanced age. This decrease in mobility is a factor that influences both their quality of life and their dependence of others in daily life. Thus, it becomes necessary to find means and tools to prevent, compensate, improve or help to restore and increase the mobility of the affected people. The main expectation is that such means help to recover or ameliorate their independence in their daily life. Traditional training employs a treadmill with a support-weight system. This training is based on the principle of repetition of all the physical movements of a gait and has shown to produce good results in terms of rehabilitation of patients. However, this therapy requires two or more therapists in assisting patients during walking, to hold and adjust the patient’s lower limbs to correctly produce the desired gait. Thus, it requires a substantial commitment and effort of the therapists [1], and it is very expensive in terms of human resources. This leads to a boost on the population healthcare and assistive services demand and, thus an increase in the need for care givers. Assistive mobility robotic devices for gait training of disabled patients in treadmills and in the ground are one successful alternative. Other alternatives include devices that allow a broader training of patients, in different ground types, and the repetition of gait movements in uphill, downhill and trip. This paper reviews state of the art training gait devices focusing on passive and active devices. Passive devices rely on the principle of Gravity-Balancing in that they try to reduce or eliminate the effects of gravity during walking. Active devices are usually classified according to three different approaches: (i) treadmillexoskeleton based devices, (ii) robotic manipulators generating different types of gait patterns, and (iii) mobilite devices. In this review, several examples of current devices are presented.